Determinants of microfinance loan repayment performance of microenterprises in Molo, Iloilo City - Dagum, Marett Andhrea S.; Lara, Nonelon L., Jr.; Lucito, Jan Rizza G.; Mendoza, Aaron James F.; Rogando, Jasper ken I.; Selibio, Ma. Emie S. (2017.)
Access to finance by microenterprises is paramount for its success. The existing microfinancetitutions (MFIs) have tried to bridge the gap of credit accessibility to microenterprises but despite this, they have been defaulting on their loans. Tis study was carried out to analyze the factors influencing loan repayment in microfinance institutions. The findings will assist the mcirofinance institutions in coming up with the most appropriate measures to apply in order to evade loan defaults. An explanatory research was employed with a target population of 100 registered MFI clients at Taytay sa Kauswagan, Incorporated (TSKI) in Molo, Iloilo City. Todetermine the sample size, convenience sampling was applied. Data was collected through the use of structured survey questionnaires and were analyzed using both descriptive and inferential statistics. The study established that number of dependents and family head are individual characteristics influencing loan repayment. Using these findings, The MFIs can pursue further growth by aiming for profitability and improvement of services. the study recommends that the borrowers with a large number fo dependents as well as family heads be supervised carefully and followed-up constantly to prevent defaults and late payments from these clients. In accordance with this, MFIs should consider evaluating and revising their credit risk management as a response to the findings of this study and involving field officers in generating policies. On the part of the borrowers, they should become more aware of their obligations and capabilities and learn to manage their resources in order to avoid defaulting or late payment of loans. Lastly, there is a need for future researches to be conducted with the same MFI focusing on the individual members of group borrowing as well as factors related to the MFIs and the loan in order to further narrow down the probable causes of poor repayment performance.
Research Paper (BA 199-Business Research) -- [Iloilo City] : Univerity of the Philippines Visayas - College of Management, May 23, 2017.